2004
DOI: 10.1007/bf02985613
|View full text |Cite
|
Sign up to set email alerts
|

Accurate scatter correction for transmission computed tomography using an uncollimated line array source

Abstract: We investigated scatter correction in transmission computed tomography (TCT) imaging by the combination of an uncollimated transmission source and a parallel-hole collimator. We employed the triple energy window (TEW) as the scatter correction and found that the conventional TEW method, which is accurate in emission computed tomography (ECT) imaging, needs some modification in TCT imaging based on our phantom studies. In this study a Tc-99m uncollimated line array source (area: 55 cm x 40 cm) was attached to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…In general, gamma‐camera imaging is performed immediately after 6 and 24 hours after injection, and in some cases tracking is required after 48 and 72 hours. However, direct evidence of CSF leakage is not well confirmed, because there are many cases of leakage below the resolution limit 51 . In our study, RNC demonstrated significantly lower sensitivity compared with the other imaging modalities.…”
Section: Discussioncontrasting
confidence: 61%
“…In general, gamma‐camera imaging is performed immediately after 6 and 24 hours after injection, and in some cases tracking is required after 48 and 72 hours. However, direct evidence of CSF leakage is not well confirmed, because there are many cases of leakage below the resolution limit 51 . In our study, RNC demonstrated significantly lower sensitivity compared with the other imaging modalities.…”
Section: Discussioncontrasting
confidence: 61%
“…Kojima et al (6) also showed that scattered photons transmitted through the object have a peak within the main energy window. Therefore, this study subtracted the Compton scatter windows (side windows) from the main window for scatter correction.…”
Section: Discussionmentioning
confidence: 99%
“…Perisinakis et al, (5) using double energy window (DEW) and TEW for scatter correction could distinguish lesions in liver studies. Akihiro Kojima et al, (6) investigated scatter correction in transmission computed tomography (TCT) imaging by the combination of an uncollimated transmission source and a parallel‐hole collimator. They employed the TEW as the scatter correction and found scattered photons transmitting through the object have a peak within the main energy window, based on their phantom studies.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have introduced many methods for eliminating the source of artifacts and for augmenting MPI accuracy ( 12 - 22 ). However, no investigations have been conducted so far on the effects of different protocols on various artifacts related to gastrointestinal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Water, milk, soda, lemon juice, and fatty meals are different substances that investigators have tested, and they are known to change the pattern of extracardiac activity in MPI; however, there is still a paucity of data in the existing literature on the possible effects of those substances on different artifacts ( 12 - 22 ). Hara et al noted that reduction of subcardiac activity can occur by drinking small amounts of soda as the result of stomach distention, drawing gastrointestinal activity away from the myocardium ( 5 ).…”
Section: Discussionmentioning
confidence: 99%